THE ROLE OF THE MAIN OBJECTS OF STUDY IN LINGUOCULTUROLOGY IN THE TRANSLATION AND NAMING OF LITERARY WORKS.: THE ROLE OF THE MAIN OBJECTS OF STUDY IN LINGUOCULTUROLOGY IN THE TRANSLATION AND NAMING OF LITERARY WORKS. - Sultonova, Nigora (Журнал иностранных языков и лингвистики, 2021)
THE ROLE OF THE MAIN OBJECTS OF STUDY IN LINGUOCULTUROLOGY IN THE TRANSLATION AND NAMING OF LITERARY WORKS.